Children’s Reader Responses to North Maluku Folklore ‎through Interactive YouTube-Based Literary Learning - Sulmi Magfirah; Dhini Yustia Widhyah; Ahmad Rifani Talaohu (Yayasan Darussalam Bengkulu, 2026)
This study examines children’s reader responses to North Maluku folklore presented through interactive YouTube-based literary learning. Drawing on reader-response theory, the study focuses on how students understand storylines, identify characters, interpret moral values, and express their interest in local folktales delivered through digital media. A descriptive qualitative design supported by simple descriptive statistics was employed. The participants were 40 students of SMP Muhammadiyah 1 Kota Ternate. Data were collected through questionnaires consisting of closed-ended and open-ended items after students watched three North Maluku folktales: Tanjung Menangis Halmahera, Air Telaga Biru, and Danau Tolire. The data were analyzed by calculating response percentages and interpreting students’ written responses thematically. The findings indicate that interactive YouTube-based media can support students’ engagement with local folklore. Most students showed positive responses to the visual and narrative aspects of the videos and were able to understand the storylines. Their interpretations mainly centered on moral values such as honesty, loyalty, humility, and rejection of greed and violence. The study also reveals that students’ familiarity with North Maluku folklore remains partial, suggesting the need to strengthen local literary learning through digital and culturally responsive media. These findings contribute to discussions on children’s literature, digital literacy, and the pedagogical use of local folklore in literary learning.